Pelaksanaan Perjanjian Kerjasama Antara Pt Aplikasi Karya Anak Bangsa Indonesia (Gofood) Dengan Mitra Usaha Penjual Di Bukit Raya - Selvi Wulandari; Firdaus Firdaus; Meriza Elpha Darnia (Peneliti.net, 2023)
Agreement, is a legal relationship (rechbetrekking) concerning the law of wealth between two or more persons (persons) or more, which gives rights to one party and obligations to the other party regarding an achievement. The agreement between PT. Application Karya Anak Bangsa which is an electronic application that distributes services and community needs, one of which is a system of buying food from home or often known as Gofood with restaurants that work together as merchants or called business partners, which is very practical in practice. obstacles often occur, such as the existence of a bill dispute where the restaurant does not get its rights as a partner of PT. Application Karya Anak Bangsa. The problems discussed are about how to implement the partnership agreement between PT. AKAB and sales partners in the field and based on the Civil Code and other laws and regulations. The study was conducted in the Bukit Raya area, while the sample population was restaurants and UMKM s in collaboration with PT. AKAB and all parties related to the problems studied in this study. The data collection methods used in this study were observation, interviews, and studies